The factors that contribute to insomnia among UiTM Kelantan students using logistic regression / Afiqah Nadia Daud, Nursyafiqa Che Ahmad and Nurul Syaza Athirah Azizi - Daud, Afiqah Nadia; Che Ahmad, Nursyafiqa; Azizi, Nurul Syaza Athirah (2019)
This study is about the factors that contribute to insomnia among UiTM students in Kelantan. The purposes of this study are to find out the occurrence of insomnia among students, to identify the association of Insomnia and Gender and to determine which factors significantly contribute to insomnia among UiTM Kelantan students. The variables that involve in this study are Insomnia as the dependent variable and independent variables are Depression, Anxiety, Stress and Life Habit. Factors that contribute to Insomnia among students are important. Mostly the students are not aware about insomnia. The appropriate sample size for this study is 255 out of 752 of UiTM Kelantan students determined by using sample size calculator Raosoft. Inc. However, only 228 respondents give cooperation for this study by answering the questionnaire. This means the response rate is 89.41 percent which is acceptable and considering good. For analysis purpose, SPSS software was used. The methodologies that involve in this study were Logistic Regression and Chi-Squared Test. As overall result, it was found that only Depression that contribute to Insomnia. For the other three which are Anxiety, Stress and Life Habit did not contribute significantly to Insomnia among students in UiTM Kelantan